Blinde Flecken und die Hoffnung auf einen Innovationsschub. Schule in der digitalen Welt - Eickelmann, Birgit; Maaz, Kai (Schule weiter denken)

Schule und Lernen angesichts der Digitalisierung – Konzepte und Befunde - Gerick, Julia; Eickelmann, Birgit (Handbuch Lernen mit digitalen Medien)

Chancengerechter Zugang zum Lernen in der digitalen Welt - Eickelmann, Birgit (SchulVerwaltung NRW. Fachzeitschrift für Schulentwicklung und Schulmanagement)

Re-Definition der digitalisierungsbezogenen Schulleitungsfunktionen in der Pandemie-Zeit und danach - Eickelmann, Birgit (PlanBD #2. Fachmagazin für Schule in der digitalen Welt)

GuTe DigiSchulen NRW. Zielsetzung und Konzeption des qualitativen Vertiefungsprojekts zur Studie ICILS 2018 NRW zu erfolgreichen digitalisierungsbezogenen Schulentwicklungsprozessen - Gerick, Julia; Eickelmann, Birgit; Feldmann, Barbara; Rothärmel, Anne (SchulVerwaltung NRW)

Design of Distributed Reconfigurable Robotics Systems with ReconROS - Lienen, Christian; Platzner, Marco (ACM Transactions on Reconfigurable Technology and Systems)
Robotics applications process large amounts of data in real time and require compute platforms that provide high performance and energy efficiency. FPGAs are well suited for many of these applications, but there is a reluctance in the robotics community to use hardware acceleration due to increased design complexity and a lack of consistent programming models across the software/hardware boundary. In this article, we present ReconROS, a framework that integrates the widely used robot operating system (ROS) with ReconOS, which features multithreaded programming of hardware and software threads for reconfigurable computers. This unique combination gives ROS 2 developers the flexibility to transparently accelerate parts of their robotics applications in hardware. We elaborate on the architecture and the design flow for ReconROS and report on a set of experiments that underline the feasibility and flexibility of our approach.

A Comparison of Machine Learning Techniques for the On-line Characterization of Tasks Executed on Heterogeneous Compute Nodes - Kashikar, Chinmay
Automation becomes a vital part in the High-Performance computing system in situational dynamics to take the decisions on the fly. Heterogeneous compute nodes consist of computing resources such as CPU, GPU and FPGA and are the important components of the high-performance computing system that can adapt the automation to achieve the given goal. While implanting automation in the computing resources, management of the resources is one of the essential aspects that need to be taken care of. Tasks are continuously executed on the resources using its unique characteristics. Effective scheduling is essential to make the best use of the characteristics provided by each resource. Scheduling enables the execution of each task by allocating resources so that they take advantage of all the characteristics of the compute resources. Various scheduling heuristics can be used to create effective scheduling, which might require the execution time to schedule the task efficiently. Providing actual execution time is not possible in many cases; hence we can provide the estimations for the actual execution time . The purpose of this master's thesis is to design a predictive model or system that estimates the execution time required to execute tasks using historical execution time data on the heterogeneous compute nodes. In this thesis, regression techniques(SGD Regressor, Passive-Aggressive Regressor, MLP Regressor, and XCSF Regressor) are compared in terms of their prediction accuracy in order to determine which technique produces reliable predictions for the execution time. These estimations must be generated in an online learning environment in which data points arrive in any sequence, one by one, and the regression model must learn from them. After evaluating the regression algorithms, it is seen that the XCSF regressor provides the highest overall prediction accuracy for the supplied data sets. The regression technique's parameters also play a significant role in achieving an acceptable prediction accuracy. As a remark, when using online learning in regression analysis, the accuracy depends upon both the order of sequential data points that are coming to train the model and the parameter configuration for each regression technique.

Ästhetik im Vormärz.

Der ‚Grund‘ des Erzählens. Norbert Scheuers „Reigen aus unendlich vielen vergessenen Geschichten“. - Eke, Norbert (Schatten aus den Felswänden. Eine Hommage an Norbert Scheuer und die Eifel. Hg. von Andreas Erb und Christof Hamann)

Mit Schere und Kleber. Herta Müllers Inszenierungen von Text-Bild-Räumen - Eke, Norbert (die horen. Zeitschrift für Literatur, Kunst und Kritik 66 (2021), Ausgabe 284: Furchtlos schreiben. Das Politische 1)

„Burleske Philosophie“. Theodor Mundts Humorkonzeption in der Abhandlung Aesthetik. Die Idee der Schönheit und des Kunstwerks im Lichte unserer Zeit (1845) - Eke, Norbert (Ästhetik im Vormärz (= FVF Jahrbuch 2020). Hg. von Norbert Otto Eke und Marta Famula.)

Ästhetik im Vormärz. - Eke, Norbert (Ästhetik im Vormärz (= FVF Jahrbuch 2020). Hg. von Norbert Otto Eke und Marta Famula.)

[zu:] Stephan Reinhardt: Georg Herwegh. Ein Biographie. Seine Zeit – unsere Geschichte. Göttingen: Wallstein - Eke, Norbert (Historische Zeitschrift)

[zu:] Harro Zimmermann: Ein deutscher Gotteskrieger? Der Attentäter Carl Ludwig Sand. Die Geschichte einer Radikalisierung. Paderborn: Ferdinand Schöningh, 2020 - Eke, Norbert (Ästhetik im Vormärz (= FVF Jahrbuch 2020). Hg. von Norbert Otto Eke und Marta Famula Bielefeld: Aisthesis Verlag 2021)

Künstliche Intelligenz in der Produktentstehung - Dumitrescu, Roman; Özcan, Leon; Ködding, Patrick; Foullois, Marc; Bernijazov, Ruslan

Influence of thickness, homogeneity, and morphology of TiO2-m nanoparticle coatings on cancer cell adhesion - Garcia-Diosa, Jaime Andrés; Orive, Alejandro Gonzalez; Grundmeier, Guido; Keller, Adrian; Camargo-Amado, Rubén Jesús (Surface and Coatings Technology)

SUSTAINABILITY THROUGH THE DIGITALIZATION: EXPLORING POTENTIALS AND DESIGNING VALUE CO-CREATION ARCHITECTURES FOR PRODUCT-SERVICE-SYSTEMS - Scholtysik, Michel; Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Digitalization and sustainability are major challenges for today's manufacturing industry. While digitalization is characterized by the incorporation of digital technologies in the products and services as well as the value creation architectures, sustainability requires them to balance economic, environmental and social issues. In both areas, especially Product Service Systems (PSS) are constantly gaining importance. This results in so called smart PSS that integrate digital technologies as well as sustainable PSS which aim at a positive impact on sustainability. Both two concepts cannot be clearly delimited since smart PSS might be designed for sustainability as well and sustainable PSS might be used with digital technologies. This paper aims to investigate the interrelations. To that, digitalization patterns of products and services are evaluated regarding their sustainable impact. The evaluation is conducted by a survey in research and industry. Furthermore, the design of the underlying value creation architecture is investigated. Here, a methodology is proposed enabling companies to optimize their value creation architecture.
Keywords: sustainability

Strategisch-technische Anforderungsanalyse - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Mehrzieloptimierte und durchgängig automatisierte Bauteilentwicklung für Additive Fertigungsverfahren im Produktentstehungsprozess)

Mehrzieloptimierte und durchgängig automatisierte Bauteilentwicklung für Additive Fertigungsverfahren im Produktentstehungsprozess - Ergebnisbericht des BMBF Verbundprojektes OptiAMix

Connecting Energy Storages from Tool Independent, Signal-flow Oriented FMUs - Ehlert, Meik; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Kalla, Matthias; Bagaber, Bakr; Ponick, Bernd; Mertens, Axel (Proceedings of the International Conference on SMACD and 16th Conference on PRIME)

Smart Service-Transformation mit Geschäftsmodellmustern - Reinhold, Jannik; Ködding, Patrick; Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Smart Services sind das Resultat zweier Megatrends: Digitalisierung und Servitisierung. Diese digitalen Dienstleistungen erfordern innovative Geschäftsmodelle, deren Umsetzung jedoch häufig eine Anpassung historisch gewachsener Wertschöpfung produzierender Unternehmen voraussetzt. Wir liefern geeignete Geschäftsmodellmuster zur Entwicklung von Geschäftsmodellen für Smart Services und zeigen, wie produzierende Unternehmen darauf aufbauend die Transformation ihrer Wertschöpfung planen können.

Relevance of fructose intake in adolescence for fatty liver indices in young adulthood - Perrar, Ines; Buyken, Anette; Penczynski, Katharina J.; Remer, Thomas; Kuhnle, Gunter G.; Herder, Christian; Roden, Michael; Della Corte, Karen; Nöthlings, Ute; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose To examine the association between fructose intake in adolescence and fatty liver indices (hepatic steatosis index (HSI), fatty liver index (FLI)) in young adulthood. Methods Overall, 246 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had a fasting blood sample in adulthood (18–36 years), at least two 3-day weighed dietary records for calculating fructose intakes and other fructose-containing sugars (total (TS), free (FS), added sugar (AS)) as well as two complete 24-h urine samples for calculating sugar excretion (fructose excretion (FE), fructose + sucrose excretion (FE + SE)) in adolescence (males: 9.5–16.5 years; females: 8.5–15.5 years) were analysed using multivariable linear regression analyses. Results On the level of dietary intake, no prospective associations were observed between adolescent fructose intake and both adult fatty liver indices, whereas higher FS intakes were associated with lower levels of HSI ( P trend = 0.02) and FLI ( P trend = 0.03). On the urinary excretion level, however, a higher FE (P trend = 0.03) and FE + SE ( P trend = 0.01) in adolescence were prospectively related to higher adult FLI values. No associations were observed between adolescent sugar excretion and adult HSI. Conclusion The present study does not provide unambiguous support for a detrimental impact of adolescent fructose intake on adult liver health. Nonetheless, further examinations estimating exposure by means of urinary excretion as well as dietary intake levels appear warranted.

The Prospective Association of Dietary Sugar Intake in Adolescence With Risk Markers of Type 2 Diabetes in Young Adulthood - Della Corte, Karen A.; Penczynski, Katharina; Kuhnle, Gunter; Perrar, Ines; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Remer, Thomas; Alexy, Ute; Buyken, Anette (Frontiers in Nutrition)
Purpose: To examine the prospective relevance of dietary sugar intake (based on dietary data as well as urinary excretion data) in adolescent years for insulin sensitivity and biomarkers of inflammation in young adulthood. Methods: Overall 254 participants of the DONALD study who had at least two 3-day weighed dietary records for calculating intakes of fructose, glucose, sucrose, total, free, added sugars, total sugars from sugar-sweetened beverages (SSB), juice, and sweets/sugar or at least two complete 24 h urine samples ( n = 221) for calculating sugar excretion (urinary fructose and urinary fructose + sucrose) in adolescence (females: 9–15 years, males: 10–16 years) and a fasting blood sample in adulthood (18–36 years), were included in multivariable linear regression analyses assessing their prospective associations with adult homeostasis model assessment insulin sensitivity (HOMA2-%S) and a pro-inflammatory score (based on CRP, IL-6, IL-18, leptin, chemerin, adiponectin). Results: On the dietary intake level, no prospective associations were observed between adolescent fructose, sucrose, glucose, added, free, total sugar, or total sugar from SSB, juice or sweets/sugar intake and adult HOMA2-%S ( p > 0.01). On the urinary level, however, higher excreted fructose levels were associated with improved adult HOMA2-%S ( p = 0.008) among females only. No associations were observed between dietary or urinary sugars and the adult pro-inflammatory score ( p > 0.01). Conclusion: The present study did not provide support that dietary sugar consumed in adolescence is associated with adult insulin sensitivity. The one potential exception was the moderate dietary consumption of fructose, which showed a beneficial association with adult fasting insulin and insulin sensitivity.

Using In Situ High-Energy X-ray Diffraction to Quantify Electrode Behavior of Li-Ion Batteries from Extreme Fast Charging - Paul, Partha P.; Cao, Chuntian; Thampy, Vivek; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew N.; Dufek, Eric J.; Nelson Weker, Johanna; Toney, Michael F. (ACS Applied Energy Materials)

Unraveling the Unconventional Order of a High-Mobility Indacenodithiophene–Benzothiadiazole Copolymer - Cendra, Camila; Balhorn, Luke; Zhang, Weimin; O’Hara, Kathryn; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Liang, Mengning; Toney, Michael F.; McCulloch, Iain; Chabinyc, Michael L.; Salleo, Alberto; et al. (ACS Macro Letters)

TaintBench: Automatic real-world malware benchmarking of Android taint analyses - Luo, Linghui; Pauck, Felix; Piskachev, Goran; Benz, Manuel; Pashchenko, Ivan; Mory, Martin; Bodden, Eric; Hermann, Ben; Massacci, Fabio (Empirical Software Engineering)
Due to the lack of established real-world benchmark suites for static taint analyses of Android applications, evaluations of these analyses are often restricted and hard to compare. Even in evaluations that do use real-world apps, details about the ground truth in those apps are rarely documented, which makes it difficult to compare and reproduce the results. To push Android taint analysis research forward, this paper thus recommends criteria for constructing real-world benchmark suites for this specific domain, and presents TaintBench, the first real-world malware benchmark suite with documented taint flows. TaintBench benchmark apps include taint flows with complex structures, and addresses static challenges that are commonly agreed on by the community. Together with the TaintBench suite, we introduce the TaintBench framework, whose goal is to simplify real-world benchmarking of Android taint analyses. First, a usability test shows that the framework improves experts’ performance and perceived usability when documenting and inspecting taint flows. Second, experiments using TaintBench reveal new insights for the taint analysis tools Amandroid and FlowDroid: (i) They are less effective on real-world malware apps than on synthetic benchmark apps. (ii) Predefined lists of sources and sinks heavily impact the tools’ accuracy. (iii) Surprisingly, up-to-date versions of both tools are less accurate than their predecessors.

Logarithmic Time MIMO Based Self-Stabilizing Clock Synchronization - Dolev, Shlomi; Prasadh Narayanan, Ram; Scheideler, Christian; Schindelhauer, Christian (NANOCOM '21: The Eighth Annual ACM International Conference on Nanoscale Computing and Communication, Virtual Event, Italy, September 7 - 9, 2021)

Von der Idee ins Modell – Virtualisierung von Workshopergebnissen im MBSE - Tissen, Denis; Hillebrand, Michael; Tschirner, Christian (Tag des Systems Engineering 2021)

The Canonical Amoebot Model: Algorithms and Concurrency Control - J. Daymude, Joshua; W. Richa, Andrea; Scheideler, Christian (35th International Symposium on Distributed Computing, DISC 2021, October 4-8, 2021, Freiburg, Germany (Virtual Conference))

Selbststabilisierender Bakery Algorithmus für verteilte Systeme - Everling, Leon

System alternatives for modular, zero-emission high-speed ferries - Lagemann, Benjamin; Seidenberg, Tobias; Jürgenhake, Christoph; Erikstad, Stein Ove; Dumitrescu, Roman (SNAME International Conference on Fast Sea Transportation)

D-REQs: Determination of security & safety requirements in workshops based on the use of model-based systems engineering - Japs, Sergej; Anacker, Harald; Kaiser, Lydia; Holtmann, Jörg; Dumitrescu, Roman; Kargl, Frank (Proceedings of the IEEE)

Smart factory reference model for training on Industry 4.0 - Mohammad, Ubaidullah; Low, Cheng; Rahman, Ramhuzaini Abd; Johar, Muhammad Akmal; Koh, Ching Theng; Dumitrescu, Roman; Rabe, Martin; Asmar, Laban; Kamaruddin, Susana (Journal of Mechanical Engineering (JMechE))

Peer-to-Peer Matching for Distributed Systems - Adsul, Vaibhav

Data-Driven Model for Upper Limb Spasticity Detection - Yee, Jingye; Low, Cheng Yee; Hashim, Natiara Mohamad; Hanapiah, Fazah Akhtar; Soh, Wei Shien; Zakaria, Noor Ayuni Che; Nemah, Mohammed Najeh; Asmar, Laban; Rabe, Martin; von Enzberg, Sebastian; Dumitrescu, Roman (International Journal of Integrated Engineering)

Selecting Features for the Next Release in a System of Systems Context - Wiecher, Carsten; Wolff, Carsten; Anacker, Harald; Dumitrescu, Roman (arXiv preprint)

Derivation of socio-technical solution patterns for industry 4.0 problem classes - Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Towards an ambidextrous innovation management maturity model - Niewöhner, Nadine; Lang, Nadja; Asmar, Laban; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Integration of agile practices in the product development process of intelligent technical systems - Gabriel, Stefan; Niewöhner, Nadine; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Development Process for Smart Service Strategies: Grasping the Potentials of Digitalization for Servitization - Koldewey, Christian; Gausemeier, Jürgen; Dumitrescu, Roman; Evers, Hans Heinrich; Frank, Maximilian; Reinhold, Jannik (Digitalization)

Developing Strategies for Digital Transformation in SMEs with Maturity Models - Pierenkemper, Christoph; Gausemeier, Jürgen (Digitalization)

Identification and specification of standard modules in production for a material flow simulation - Henkenjohann, Mark; Joppen, Robert; Köchling, Daniel; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Iterative and Scenario-Based Requirements Specification in a System of Systems Context - Wiecher, Carsten; Greenyer, Joel; Wolff, Carsten; Anacker, Harald; Dumitrescu, Roman (Requirements Engineering: Foundation for Software Quality, REFSQ 2021)

Changes in chronotype and social jetlag during adolescence and their association with concurrent changes in BMI-SDS and body composition, in the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Krüger, Bettina; Nöthlings, Ute; Buyken, Anette E.; Alexy, Ute (European Journal of Clinical Nutrition)
Abstract Background/objectives Adolescence is a critical period for both the development of overweight and the transition toward a later chronotype, often accompanied by an increase in social jetlag. This study assessed whether changes in chronotype and social jetlag, are linked to changes in body composition during adolescence. Subjects/methods We used data from the DONALD open cohort study, collected between 2014 and 2019, from 213 adolescents (9–17 years at baseline, 45% females) having at least two measures of chronotype and anthropometry ( N = 572). Chronotype was assessed with the Munich Chronotype Questionnaire and defined as: midpoint of sleep corrected for sleep-debt (MSFsc) accumulated over the week (later MSFsc represents later chronotype). Social jetlag (SJL) defines the difference between midpoint of sleep during week and weekend. Calculations for Fat Free Mass Index (FFMI [kg/m 2 )]) and Fat Mass Index (FMI) [kg/m 2 )]) were based on body fat percentage, weight, and height. To analyze the associations, we used linear mixed-effect regression models. Finally, the total cohort was split into three biologically relevant age groups (cut-off set at <12 years, ≥12 to ≤15 years and >15 years). Results Median follow-up was 2.1 years. Overall, change toward a later chronotype was significantly related with an increase in FMI (ß: 0.05, 95% CI: 0.01–0.08). A 1 h increase in social jetlag predicted an increase in BMI-SDS of 0.08 SDS units (95% CI: 0.01–0.14) and in FMI of 0.04 kg/m2 (95% CI: 0.003–0.08). Associations were stronger for the age group ≥12 to ≤15 years ( p for interaction: <0.001). No relationship was found with FFMI. Conclusions Changes in MSFsc and SJL during adolescence were associated with concurrent changes in BMI-SDS and FMI. The age ≥12 to ≤15 years appears to be a sensitive period in which chronobiological changes were clearly associated with increasing body fatness.

Model of a Triangular Caterpillar Drive and Analysis of Vertical Vehicle Dynamics - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Russian Engineering Research)

Arbeit 4.0 in der Produktentstehung mit IviPep - Foullois, Marc; Kato-Beiderwieden, Anna-Lena; Mlekus, Lisa; Maier, Günter W.; Jenderny, Sascha; Röcker, Carsten; Dietz, Oliver; Pretzlaff, Matthias; Huxdorf, Oliver; von Dungern, Friedrich; Bräutigam, Dieter; Seifert, Lars; et al. (Arbeit in der digitalisierten Welt - Praxisbeispiele und Gestaltungslösungen aus dem BMBF-Förderschwerpunkt)

Platform Patterns - Using Proven Principles to Develop Digital Platforms - Drewel, Marvin; Özcan, Leon; Gausemeier, Jürgen; Dumitrescu, Roman (Journal of the Knowledge Economy)
Hardly any other area has as much disruptive potential as digital platforms in the course of digitalization. After serious changes have already taken place in the B2C sector with platforms such as Amazon and Airbnb, the B2B sector is on the threshold to the so-called platform economy. In mechanical engineering, pioneers like GE (PREDIX) and Claas (365FarmNet) are trying to get their hands on the act. This is hardly a promising option for small and medium-sized companies, as only a few large companies will survive. Small and medium-sized enterprises (SMEs) are already facing the threat of losing direct consumer contact and becoming exchangeable executers. In order to prevent this, it is important to anticipate at an early stage which strategic options exist for the future platform economy and which adjustments to the product program should already be initiated today. Basically, medium-sized companies in particular lack a strategy for an advantageous entry into the future platform economy. The paper presents different approaches to master the challenges of participating in the platform economy by using platform patterns. Platform patterns represent proven principles of already existing platforms. We show how we derived a catalogue with 37 identified platform patterns. The catalogue has a generic design and can be customized for a specific use case. The versatility of the catalogue is underlined by three possible applications: (1) platform ideation, (2) platform development, and (3) platform characterization.
Keywords: Digitalization; Digital platforms; Platform economy; Multisided markets; B2B platforms

Towards collaborative life cycle specification of digital twins in manufacturing value chains - Rasor, Rik; Göllner, Denis; Bernijazov, Ruslan; Kaiser, Lydia; Dumitrescu, Roman (Procedia CIRP)

Structuring Framework for Early Validation of Product Ideas - Asmar, Laban; Grigoryan, Khoren; Low, Cheng Yee; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (International Journal of Integrated Engineering)

Improving Real-World Applicability of Static Taint Analysis - Luo, Linghui